Book Review : Human Drama Inc. Emotional Intelligence in the Workplace - Sharma, Devika Rani (Prabandhan: Indian Journal of Management, 2017)
The book review analyzed Neeta Mohla's book - Human Drama Inc. Emotional Intelligence in the Workplace. The author, through this book, showcased various insights of emotional intelligence from an organization's perspective. The author depicted through the book how an employee can make his/her organization a better place to work by displaying the right emotions.